Effects of stress and relaxation on pain perception in subjects with pain‐free occlusional disharmony compared with healthy controls. (17th November 2014) - Ruscheweyh, R; Becker, T; Born, Y; Çolak‐Ekici, R; Marziniak, M; Evers, S; Gerlach, AL; Wolowski, A
Abstract : Objectives: The significance of occlusal disharmony for the development of painful temporomandibular disorder (TMD) is controversial. The ongoing biomechanical strain caused by occlusal disharmony might lead to sensitization processes in the nociceptive system. Understanding these processes might be an important step toward understanding the possible relationship between occlusal disharmony and TMD. In this study, we therefore investigated whether subjects with occlusal disharmony ( n = 22) differ from healthy controls ( n = 26) in their pain perception and pain modulation by stress and relaxation. Materials and Methods: Trigeminal and extratrigeminal experimental pain perception (pinprick, heat, and pressure pain) was assessed before and after stress (mental arithmetic) and relaxation (viewing of low‐arousal pictures). Results: There were no group differences in pain perception at baseline or during the stress task. Compared with controls, the occlusal disharmony group exhibited an inadequate reduction in pain perception during relaxation, which was significant for the extratrigeminal site ( P < 0.01) and reached a trend for significance at the trigeminal site ( P = 0.1). Conclusions: These results suggest that subjects with occlusal disharmony show signs of disturbed endogenous pain inhibition during relaxation. Clinical Relevance: There is evidence for the presence of sensitization of the nociceptive system in subjects with occlusal disharmony. Possibly, deficient inhibition of extratrigeminal and trigeminal pain perception by relaxation might contribute to the development of TMD or other chronic pain disorders.